Helical Coil Compression Spring Retrofit Design of Wheelbarrow for Optimal Load Carrying Effectiveness - Agbo, Cornelius Ogbodo Anayo (Makara Journal of Technology, 2025)
Wheelbarrows are essential multipurpose and dual-function materials handling equipment for many industries and homes. They find exclusive use in the movement of finished goods and raw materials where no other form of transportation works. However, the traditional wheelbarrows require enormous human effort to accomplish the task of conveying a reasonable amount of load from one place to another. During the process, shock loads from road irregularities are transmitted directly to the Barrow pusher. Therefore, this study investigated a retrofitted helical coil, compression spring, wheelbarrow design for effective load transportation. A wheelbarrow with a trapezoidal bucket capacity of 50 l was fabricated and mounted on a hollow pipe galvanized steel chassis frame. The bucket was supported on the front end of the frame using two helical coil compression springs to cushion the shock loads transmitted to the Barrow pusher. For a 150-kg payload, three standard bags of cement equivalent, and a deadweight of 22kg, the spring retrofit design wheelbarrow effectively reduces the galloping shocks through bumps and other path surface irregularities better than conventional non-spring wheelbarrows. The new design can therefore provide succor to the regular wheelbarrow pushers who tend to develop unintended health issues, such as muscular build-up and cramps, as they use a wheelbarrow to move materials over a distance.